Research on Flight Operational Quality Assurance Based on ROM Concept. Issue 2 (March 2019) - Wang, Haofeng; Qi, Kai; Tang, Yin
Abstract: The flight operational quality management method based on Routine Operational Measure (ROM) can visually find hidden insecurity factors during flight operation and provide pilots directions in enhancing technologies and risk warning by completing collection off light segment data of aircrafts in routine operations and carrying out the analysis and research on flight data. Based on the theoretical analysis and the needs of airlines, this paper designs and implements the flight operational quality management system based on ROM so that the flight operational quality management of civil aviation of China can realize its critical transformation from a fleet to an individual and from ex-post to ex-ante.